Consequences of microhabitat selection for reproductive success in the parasitic copepod Neobrachiella spinicephala (Lernaeopodidae) - Timi, Juan Tomas (2010)
Narrow site specificity in parasites is assumed to be associated with fitness benefits, such as higher reproductive success, although this is never quantified. We linked the body mass and combined mass of egg sacs of female copepods, Neobrachiella spinicephala, parasitic on the sandperch, Pinguipes brasilianus, to attachment sites on the host. Adult females attach permanently either on the lips, the margins of the operculum, or the base of pectoral or pelvic fins. In addition to influences of sampling site, season and host body length, our analyses revealed important fitness effects. First, attachment site significantly influenced copepod body mass; independent of other factors, copepods at the base of fins were 32% larger than those on the lips or operculum. Second, the mass of egg sacs was almost always greater if the copepod was attached at the base of fins rather than to the lip or operculum. Thus, a female weighing 6 mg would, on average, produce 40% larger egg sacs if attached to the base of fins. However, copepods were much more likely to attach at the base of fins on small fish, and on either the lip or the operculum on large fish. We propose that constraints varying with fish size account for the shift from optimal to suboptimal attachment sites as a function of increasing host size. By measuring differences in fitness components between attachment sites, our approach allows hypothesis testing regarding microhabitat selection.